Effective schools for disaffected students : integration and segregation - Cooper, Paul, 1955- (Routledge, 1993)
Disaffected pupils respond well in circumstances where they feel secure, where they have a sense of being valued and respected, and where they perceive there to be opportunities for them to succeed. Effective Schools for Disaffected Students offers insights into how these outcomes might be achieved in both mainstream and segregated settings. The investigation is based on the views of pupils who have been excluded from mainstream schools for pupils with emotional and behavioural difficulties. The author relates the pupils' experiences of the different types of school to research in.